Use of orcein in detecting hepatitis B antigen in paraffin sections of liver. - Kirkpatrick, P (1982)
This study has shown that different supplies/batches of orcein perform differently and may fail. The "natural" forms generally performed better although the most informative results were obtained with a "synthetic" product. Orcein dye solutions can be used soon after preparation and for up to 7 days without the need for differentiation. After 10 days or so the staining properties become much less selective. Non-specific staining severely reduces contrast and upon differentiation overall contrast is reduced and the staining of elastin is reduced. Copper-associated protein positivity gradually fails and after 14 days is lost. For demonstrating HBsAg in paraffin sections of liver, it is best to use orcein dye preparations that are no older than 7 days and to test each batch or orcein against a known positive control.